THE RELATIONSHIP BETWEEN THEORY AND PRACTICE LEARNING ON SHOOTING LEARNING OUTCOMES IN FUTSAL GAMES - Hidayatullah, Alfian; Yono, Topo; Difitriyani, Herma (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
Education is something that must be embedded in humans. One way to obtain education is through school. Schools are institutions that provide various types of education such as knowledge, character, morals and so on. Physical Education is one of the education to improve the quality of humans who have noble character, are intelligent and physically and mentally healthy in humans. The world of education in school educational institutions cannot be separated from the learning methods provided so that the knowledge conveyed can be well received by educated students. This study aims to examine the relationship between theoretical learning and the relationship to the results of shooting learning in futsal games on the learning outcomes of students at Nogosari 06 Elementary School. The population in this study were students at Nogosari 06 Elementary School with a research sample of 14 fifth grade students. This study is a correlational research with a survey method. The results obtained from this study indicate that there is a positive and significant relationship between theoretical and practical learning on the learning outcomes of students at Nogosari 06 Elementary School. In addition, the theoretical learning method has a stronger relationship than the practical learning method on the learning outcomes of students at Nogosari 06 Elementary School. Therefore, it is recommended that teachers in charge of PJOK subjects pay more attention to how to practice existing theories so that they are easier for students to understand.